The Epistemology of Dissent: Ritual, Counter-Memory, and Hermeneutic Sovereignty among Shi'a Muslims in Garut, Indonesia - Hani Hanifah; Asep Burhanuddin (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2026)
This article advances the thesis that the distinctive ritual practices of Indonesia’s Shi’a Muslim communities tawassul (intercessory supplication through the Ahl al-Bayt), the commemoration of Ashura (10 Muharram), and the commemoration of Ghadir Khum (18 Dhu al-Hijja) function not primarily as expressions of devotional piety but as epistemological operations through which a minority community constructs and defends its hermeneutic sovereignty against majoritarian pressure. Drawing on phenomenological hermeneutics (Ricoeur), Shi’a Islamic philosophy (Corbin, Mulla Sadra), and the theory of corporeal counter-memory (Connerton), this article analyzes ethnographic data from the Majelis Tahlil dan Shalawat community in Ciparay, Garut Regency, West Java. Three key propositions are developed: tawassul enacts an ontological hierarchy of being grounded in Mulla Sadra’s tashkik al-wujud; Ashura operates as a mechanism of corporeal counter-memory that transmits a counter-historiography against the Sunni majoritarian narrative; and Ghadir Khum functions as a performative speech act (in Austin’s sense) that renews the community’s claim to an epistemic lineage running from the Prophet through the Ahl al-Bayt. The article argues that the Glock-Stark religiosity framework dominant in Indonesian Islamic studies is structurally inadequate to capture this epistemological dimension, given its Protestant-derived belief-first assumption. It further argues that Indonesia’s religious tolerance discourse requires reconceptualization beyond equal recognition of devotion toward acknowledgment of minority epistemic sovereignty in the sense theorized by Miranda Fricker.